Penerapan Metode Achievement Grouping Mata Pelajaran PAI di SMK Madinatul Ulum Pasinan Bauerno Bojonegoro - Fahru Rozi; Farida Isroani (Jurnal Bahastra, 2020)
Islamic Religious Education is important to give birth to a generation of people who are not only smart but also have good morals and character, for that in learning teachers must choose the right method, the use of the Achievement Grouping method is used to support students' understanding of Islamic Religious Education material. at SMK Madinatul Ulum, is an educational institution that applies the Achievement Grouping Method, grouping students based on their achievements. This study aims to reveal the implementation of learning by grouping based on their achievements. The problems that arise in these activities are the lack of time for implementation and the emergence of perceptions among students that students with low achievements should not be friends with high ones or vice versa. The method used is a qualitative research that shows the implementation of the Achievement Grouping Learning Method in Islamic Religious Education subjects by grouping students based on abilities that allow teachers to understand the level of understanding of the material they are studying. The teacher prepares learning tools including student score data as a reference in grouping. The Achievement Grouping method brings a positive role for students, as evidenced by the results of student evaluations which show an increase in both smart and less intelligent students, showing the students' grasp of the material being taught. Limited time is the main obstacle in implementing the Achievement Grouping Method and the emergence of an understanding of friends according to their achievements. Giving an understanding by the teacher about the use of the Achievement Grouping Method is the right solution. The results of this study indicate an increase in student learning outcomes and an increase in students' understanding of Islamic Religious Education materials at SMK Madinatul Ulum Vocational School after the use of the Achievement Grouping Method.